Folkesundhed og disciplinering - kulturanalyse af en opdragelsesstrategi - Christiansen, Ask Vest (Forum for Idræt, 2000)
Analyse af regeringens folkesundhedsprogram 1999-2008 set i relation til ændringen af sygdomsbilledet siden 1900-tallet og diskussion af det nuværende sundhedspolitiske syn på idrætten. Public health and discipline – a cultural analysis of a strategy for instruction In May 1999 the Danish Government’s Public Health Programme 1999-2008 was published. This article argues that the public health programme was developed as one element in a general slimming down of the welfare state. It will not be possible to maintain standards of welfare unless individuals and social institutions alike undergo a process of slimming down. Seen in this way, the public health programme is part of a project to impose social discipline and order. What has to be regulated is people’s behaviour so that it can become acceptable from the point of view of health. This is made necessary due to changes in the structure of illness during the past century, which in turn have prompted a change in medical focus away from cure and towards prevention. Prevention is a strategy which makes considerable use of a form of risk-moralising which directs itself by and large towards all areas of human activity. The public health programme has in this way changed its focus of operation from a social level to a subject- based, individual level. From this arises a paradox in regard to guilt and responsibility. On the one hand responsibility is taken away from the individual partly by dint of the interference of the state – for example, in relation to smokers – and partly through the way in which plans for prevention manifest themselves. On the other hand there is a tendency towards increased feelings of guilt. The result of this is that a large number of our everyday actions are placed in a health context. Health can no longer be taken for granted but is something to which we have to devote constant attention. The surveillance of health, which was once the task of the medical police, has now become integrated into the life of the individual and has turned into self-surveillance. This indicates that the health project is more concerned with moral than with medical matters.